Humanitarian Issues in the Novel Kenang-Kenangan Mengejutkan Si Beruang Kutub By Claudio Orrega Vicuña: A Psychological Study of Literature - Muhammad Iqbal Ibrahim; Nurhadi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research is motivated by the increasing phenomenon of animal cases that are victims of violence and human exploitation. The problems in this study include how the theme, plot, characterization, how the character's personality, and humanitarian problems are in the novel Kenang-kenangan Mengejutkan si Beruang Kutub. This study has the aim of describing the theme, plot, and characterization, character personality, and humanitarian problems in the novel Kenang-kenangan Mengejutkan si Beruang Kutub. The research method used is descriptive qualitative with the data source of the novel Kenang-kenangan Mengejutkan si Beruang Kutub. The results of the analysis show that the character's personality structure is interconnected between the id, ego, and superego which form the character's psyche in viewing problems that exist in humans. The researcher found four humanitarian problems, namely problems between humans and animals, humans, power, and routines